The oncology nurse coordinator: role perceptions of staff members and nurse coordinators - Liza Monas; Orly Toren; Beatrice Uziely; David Chinitz (BMC, 2017)
Abstract Background There is extensive evidence that the role of nurse coordinators is beneficial for patients. Nurse coordinators are more available to patients compared to general registered nurses, know better to control symptoms and work as team players with multiple care providers. Despite its significance, there is a dearth of literature on the subject in Israel and a lack of clarity regarding the definitions of the role in terms of responsibilities and authorities. The aim of the study is to: To examine how the role of nurse oncology coordinator is implemented in various fields of oncology and to describe the actual performance of different kinds of oncology nurse coordinators and staff perceptions regarding this role in one tertiary hospital in Jerusalem. Methods A phenomenological approach was used to explore the participants' experiences and views of nurse coordinators' performance. We conducted a qualitative study using in-depth semi-structured interviews. Interviewees included 30 employees from different levels of the hospitals, and leading figures associated with oncology medicine outside of the hospital: Nurses and physicians of the Sharett Oncology Institute of Hadassah Ein Kerem Hospital in Jerusalem, the administrative staff of Hadassah Ein Kerem Hospital, head nurses of the Israel Cancer Association, the chairperson of the Non-Profit Organization of Oncology Nurses, nurse directors at the Ministry of Health Nursing Division, and seven nurse coordinators at Hadassah Ein Kerem Hospital in diverse fields of oncology. Results The nurse coordinator is perceived as an important staff member providing care to cancer patients. Several key elements were found to be common features in the work of all nurse coordinators: emotional support, guidance to patients, and coordination of patients' care. Conclusions The nurse coordinator plays a noteworthy role in the health care system. In view of the variety of roles that the nurse coordinator assumes in different units, performance standards must be adapted to the performance areas for each unit, as well as nurses' professional development requirements. Changes in a service organization and careful attention to the continuum of care highlight the need to develop and to strengthen the role of a nurse who coordinates treatment over the entire continuum of care, both in the hospital and in the community.